2007
DOI: 10.1093/icc/dtm003
|View full text |Cite
|
Sign up to set email alerts
|

Learning, product innovation, and firm heterogeneity in developing countries; Evidence from Tanzania

Abstract: Using firm data, this study investigates the various sources of firm learning, investment and linkages, and their importance for product innovation in Tanzania.The analysis reveals important differences in innovation strategies for foreign and local firms. Foreign innovative firms have stronger vertical linkages with other foreign firms and invest more in human and physical capital. Local firms offset these disadvantages through in-house R&D, connectivity, and collaboration with other local firms, proving to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(89 citation statements)
references
References 39 publications
(30 reference statements)
4
80
1
4
Order By: Relevance
“…We thus follow prior literature ( [44], [47] & [48]) and model innovation using a logit specification. Our initial empirical model is given by INNOij = β0 + β1 + β2Corrij + XijβX + βθθij + εij where INNOij is a dummy variable indicating the innovation activity of the i-th firm at time j, Xij is a vector of observable factors that affect innovation of the firm, θij is an unobservable factor and εij is a classical random error term.…”
Section: Research Approach and Data Description Estimation Strategymentioning
confidence: 99%
“…We thus follow prior literature ( [44], [47] & [48]) and model innovation using a logit specification. Our initial empirical model is given by INNOij = β0 + β1 + β2Corrij + XijβX + βθθij + εij where INNOij is a dummy variable indicating the innovation activity of the i-th firm at time j, Xij is a vector of observable factors that affect innovation of the firm, θij is an unobservable factor and εij is a classical random error term.…”
Section: Research Approach and Data Description Estimation Strategymentioning
confidence: 99%
“…In the context of developing income countries, the lack of data at longitudinal level and the fact that for the vast majority of firms R&D activities are only a marginal determinant in innovation activities have posed several challenges in modelling innovation and growth. Nonetheless, in the recent years an increasing number of empirical studies have analysed the role of innovation in LICs firms, both exploring its determinants (Goedhuys, 2007;Robson et al, 2009) and the impact it has on various firm performance indicators (Gebreeyesus, 2009;Goedhuys et al, 2008Goedhuys et al, , 2014. Most of the latter studies focus on product and process innovation and their impact on productivity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Cirera (2015) found no link between knowledge capital investment and product innovation in Kenya. Further, Goedhuys (2007) who examined the main drivers of productivity in Tanzanians" firms and found no link between R&D, product and process innovations, licensing of technology, or training of employees, and productivity. However, it contradicts a study conducted by De (2014) that found that human and financial capital was significant in the innovation process.…”
Section: Regression Resultsmentioning
confidence: 99%
“…Goedhuys (2007) examined the main drivers of productivity in Tanzanians" firms. The author did not find any link between R&D, product and process innovations, licensing of technology, or training of employees, and productivity.…”
Section: Literature Reviewmentioning
confidence: 99%